MUSICAL EDUCATION AND PANDEMIC:: A CASE STUDY IN INSTRUMENT CLASSES USING NEW METHODOLOGIES ACTIVE IN THE HAYDÉE FRANÇA AMERICANO STATE CONSERVATORY OF MUSIC - da Silva Cortez, Alexandre (Revista Gênero e Interdisciplinaridade, 2021)
This article aims to bring an experience report of the teaching of musical instrument (acoustic guitar/electric guitar) in the form of case study at the Conservatório Estadual de Música Haidée França Americano (CEMHFA) in Juiz de Fora – MG, based on the context of the Covid-19 pandemic. The classes were ministrated online, using a methodological blend, in order to employ new active learning methodologies such as Project-Based Learning and Problem-Based Learning. The first part of the article consists of a reflection on the methodologies used in conservatories in general, and the problematization of them in current contexts, aspects of the institution’s Guitar and Guitar course were later explained, followed by an description of my experience as a teacher of these subjects in the first semester of work teaching such subjects. For the production of this work, a bibliographical research was carried on Education and Music Education, contextualizing the teaching of instrument along with the contemporary challenges on this area, focusing particularly on professional courses in music. It is therefore concluded that the use of Active Methodologies may entail significant learning situations for both students and teachers, maintaining the engagement of students in the discipline, thus creating a rich environment for the exchange and construction of knowledge.